2009
DOI: 10.1074/jbc.m109.028498
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycan Modulation of Wnt5A Signal Transduction in Metastatic Melanoma Cells

Abstract: Heparan sulfate proteoglycans (HSPGs) are important modulators for optimizing signal transduction of many pathways, including the Wnt pathways. We demonstrate that HSPG glycosaminoglycan levels increased with increasing metastatic potential of melanoma cells. Previous studies have demonstrated that Wnt5A increases the invasiveness of melanoma cells. We further demonstrate that HSPGs potentiate Wnt5A signaling, since enzymatic removal of the HSPG backbone resulted in a decrease in cellular Wnt5A levels, an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 48 publications
3
66
0
1
Order By: Relevance
“…It has also been shown that GPCs and SDCs affect distinct intracellular pathways of Wnt signaling (Alexander et al, 2000;Capurro et al, 2005a;De Cat et al, 2003;Munoz et al, 2006;O'Connell et al, 2009;Ohkawara et al, 2003). In this study, we demonstrated that GPC4 activates both the b-catenin-dependent and -independent pathway of Wnt signaling and that GPC4 ectodomain released from the cell surface membrane inhibits Wnt signaling.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It has also been shown that GPCs and SDCs affect distinct intracellular pathways of Wnt signaling (Alexander et al, 2000;Capurro et al, 2005a;De Cat et al, 2003;Munoz et al, 2006;O'Connell et al, 2009;Ohkawara et al, 2003). In this study, we demonstrated that GPC4 activates both the b-catenin-dependent and -independent pathway of Wnt signaling and that GPC4 ectodomain released from the cell surface membrane inhibits Wnt signaling.…”
Section: Discussionmentioning
confidence: 50%
“…SDC4 has been shown to bind to Fz7 and Dvl and to be required for convergent extension in Xenopus (Munoz et al, 2006). Expression of SDC1 and SDC4 correlates with Wnt5a expression in melanoma cell lines, and knockdown of SDC1 and SDC4 decreases cell invasion activity, which is restored by Wnt5a (O'Connell et al, 2009). Thus, whether the action of HSPG is positive or negative for the b-catenin-dependent or -independent pathway might in part be dependent on the type of cell or tissue.…”
Section: Introductionmentioning
confidence: 99%
“…SDC4 overexpression or knockout compromises cell migration in normal (5) and tumorigenic cells (6). More recently it was demonstrated that SDC4 is required for localization of Rac1 and membrane protrusion formation at the leading edge to allow celldirected migration (7).…”
mentioning
confidence: 99%
“…Syndecans play important roles in different physiological functions, including embryo development, vasculation, neural migration, signaling, inflammation, angiogenesis, and focal adhesion (3)(4)(5)(6)(7). There are four members of the syndecan family in vertebrates, as follows: syndecan-1, -2, -3, and -4.…”
mentioning
confidence: 99%